The Influence of Ethno Pedagogy Approach and Interpersonal Intelligence on the Results of Civic Education Learning in Pelangi Elementary school Medan - Indah Syasmita; Deni Setiawan; Daulat Saragi (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2019)
This study aims to: (1) Know the differences in the learning outcomes of KDP students who are taught with the ethno pedagogical approach compared to students who are taught with the conventional approach; (2) Knowing the difference in Civic education learning outcomes of students who have high interpersonal intelligence compared to students who have low interpersonal intelligence; (3) Knowing the interaction between learning approaches and interpersonal intelligence in influencing student learning outcomes Civic education in Pelangi Medan Private Elementary School located on Jl. Bayangkara No. 417 Medan. The population in this study was the fifth grade students at Pelangi Private Elementary School, totaling 54 people. Class V / a as many as 27 students and V / b as many as 27 students. Collecting data in this study through interpersonal intelligence questionnaires and Civic education learning outcomes test instruments. Hypothesis testing is done by the Two Way Anova test. The results showed that: (1) The learning outcomes of Civic education students who were taught with the ethno pedagogical approach were higher than the learning outcomes of Civic education students who were taught with conventional approaches (Fcount = 21.164 and a value of sig. 0.000> 0.05); (2) Civic education learning outcomes of students who have high interpersonal intelligence are higher than those of students who have low interpersonal intelligence (Fcount = 6.756 and sig. 0.012> 0.05); (3) There is an interaction between learning approaches and interpersonal intelligence in influencing student learning outcomes Civic education (Fcount = 7.054 and sig. 0.011> 0.05).